Выразите из формулы !!!!!!!!m4!!!!!!!

L*m1+c1*m1*(t3-t2)=c2*m2*(t3-t1)+c3*m3*(t3-t1)+L*(m1-m4)

1

Ответы и объяснения

2012-10-31T19:56:37+04:00

L*m1+c1*m1*(t3-t2)=c2*m2*(t3-t1)+c3*m3*(t3-t1)+L*(m1-m4) 

L*m1+c1*m1*(t3-t2)-c2*m2*(t3-t1)-c3*m3*(t3-t1)=L*(m1-m4) 


(m1-m4)=(L*m1+c1*m1*(t3-t2)-c2*m2*(t3-t1)-c3*m3*(t3-t1)) /L

-m4=-m1+ (L*m1+c1*m1*(t3-t2)-c2*m2*(t3-t1)-c3*m3*(t3-t1))/L

m4=m1- (L*m1+c1*m1*(t3-t2)-c2*m2*(t3-t1)-c3*m3*(t3-t1))/L=

 

=(L*m1-L*m1-c1*m1*(t3-t2)+(c2*m2*+c3*m3*)(t3-t1))/L=

=((c2*m2*+c3*m3*)(t3-t1)-c1*m1*(t3-t2))/L